Recent advances in aluminium matrix composites reinforced with graphene-based nanomaterial: A critical review. (July 2022) - Lava Kumar, P.; Lombardi, A.; Byczynski, G.; Narayana Murty, S.V.S.; Murty, B.S.; Bichler, L.
Abstract: In recent years, aluminium (Al) matrix reinforced with graphene-based nanomaterial (GN) composites (AGNCs) have emerged as a potential candidate for various applications due to their lightweight combined with excellent mechanical, tribological, thermal, and electrical properties. This paper is intended to provide a comprehensive and critical review of the state-of-the-art research activities related to the processing, properties, and applications of AGNCs. The review begins by highlighting the need for "lightweighting" and AGNCs, followed by a short introduction to the structure and properties of GNs. It covers the current challenges in the processing of AGNCs, such as low wettability, interfacial reactions, and agglomeration of GNs. Different consolidation and post-processing techniques used for the fabrication of AGNCs are also presented. Subsequently, the effect of GN addition on properties of AGNCs is critically reviewed. Different micromechanical models used for quantifying the strengthening of AGNCs aided by various strengthening mechanisms are also elucidated. More importantly, based on the reported properties, the potential and promising applications of AGNCs in various industries, such as automobile, aerospace, space, electrical, electronics, and energy systems, have been proposed. Afterwards, the current understanding of AGNCs is thoroughly summarized. Finally, directions for future research in the field of AGNCs have been suggested.